Development Of Rice Starch Microneedles For Drug Delivery To The Skin - Mahmood Alrimawi, Bilal Harieth (2023)
Microneedles (MNs) are minimally invasive biomedical devices that help drugs to bypass the skin barrier, resulting in systemic and localised pharmacological effects. Dissolving MNs are associated with high patient compliance and lower cross-contamination risk as compared to other MN types. Rice starch (RSC) has a high potential to be used in the development of dissolving MNs owing to its good film-forming properties, biodegradability, non-toxicity, and low cost. However, formulation of dissolving MNs using RSC is challenging due to the inherent brittleness of RSC. This thesis aims to explore RSC as a biopolymer for the fabrication of dissolving MN for drug delivery to the skin. Formulation of dissolving MNs with neat RSC was impossible due to the poor mechanical properties of RSC. Therefore, polymer blends of RSC with polyvinyl alcohol (PVA) or polyvinyl pyrrolidone (PVP) were initially used to develop films as a preliminary investigation before MN development. The addition of PVA or PVP enhanced the mechanical strength and dissolution of RSC-based films. Meanwhile, characterisation of different RSC blends demonstrated that MNs formulated with RSC blends using 20 %w/w of PVA (PVA20-MN) or 40 %w/w of PVP (PVP40-MN) showed intact needle formation with sufficient mechanical strength, skin insertion and dissolution within 60 min.